2009
DOI: 10.1111/j.1708-8208.2009.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

The Peri-Implant Sulcus Compared with Internal Implant and Suprastructure Components: A Microbiological Analysis

Abstract: Intra-coronal compartments of screw-retained fixed restorations were heavily contaminated. The restorative margin may have been the principal pathway for bacterial leakage. Contamination of abutment screws most likely occurred from the peri-implant sulcus via the implant-abutment interface and abutment-prosthesis interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
2
21

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 24 publications
5
93
2
21
Order By: Relevance
“…. Cosyn et al (2009), in a short clinical evaluation, have found similarities in the microbiota of samples collected from the internal parts of implants and from their related peri-implant sulci. Another investigations indicated that the existing oral microbiota prior to implant placement is determinant to the establishment and maintenance of the implant related microbiota..…”
Section: Biofilm Formationmentioning
confidence: 98%
See 3 more Smart Citations
“…. Cosyn et al (2009), in a short clinical evaluation, have found similarities in the microbiota of samples collected from the internal parts of implants and from their related peri-implant sulci. Another investigations indicated that the existing oral microbiota prior to implant placement is determinant to the establishment and maintenance of the implant related microbiota..…”
Section: Biofilm Formationmentioning
confidence: 98%
“…With time, strict gram-negative anaerobes as Fusobacterium spp and Prevotella spp become increasingly predominant (Mombelli & Mericske-Stern, 1990). Several reports on the microbiota detected around dental implants were published in the last decade (Haffjee et al .,1998;Botero et al, 2005;Cosyn et al, 2009;Van Brakel, et al 2010). Presence of potential periodontal pathogens colonizing the peri-implant grooves in unsuccessful implants has also been described (Laine et al, 2005;Shibli et al, 2007;Persson et al, 2010).…”
Section: Biofilm Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to last year, no evidence was available for induction of peri-implant mucositis or peri-implantitis by internal bacterial contamination. However, some studies have shown internal bacterial infiltration of the implant cavity from an external source and vice versa 10,28,29) . Contamination can be caused by external bacteria trapped during prosthetic placement or as a result of leakage at the implant-abutment interface ( Fig.…”
Section: Introductionmentioning
confidence: 99%